Bending, compression and bonding performance of cross-laminated timber (CLT) made from Malaysian fast-growing timbers - Mohamad Bhkari, Norshariza; Lum, Wei Chen; Azmi, Anis; Nordin, Muhammad Shaiful; Wong, Norman Shew Yam; Ahmad, Zakiah; Lee, Seng Hua (Tech Science Press, 2022)
This study investigated the bending, compression as well as the bonding performance of CLT panels made from fast-growing timber species, i.e., Laran (Neolamarckia cadamba) and Batai (Paraserianthes falcataria). The variables studied were timber species (Laran and Batai), layers of lamination (3-layer and 5-layer), loading direction in bending (in-plane and out-of-plane), loading direction in compression (x-, y-, and z-axis) and different treatment conditions for bonding performance test. The desired outputs of this study were bending and compression properties (strength and stiffness) as well as bonding performance (block shear strength, wood failure percentage and delamination value). The bending and compression test were conducted according to EN16351:2015 and EN408:2012, respectively. On the other hand, the bonding performance test was determined by block shear and delamination test based on EN16351:2015 and EN14374:2004, respectively. Prior to block shear test, the samples were subjected to three different treatment conditions. The results showed that CLT made from 3-layer Laran timber, loaded at out-of-plane direction exhibited the highest bending properties. Contrarily, CLT made from 5- layered Batai timber, loaded at in-plane direction showed the lowest bending properties. Laran samples for compression loaded at x-axis exhibited the best compressive properties. Generally, Laran CLT showed greater bonding performance determined by shear test compared to Batai CLT for both 3- and 5-layer panels. On the contrary, delamination results showed that Batai CLT demonstrated better bonding performance compared to Laran CLT. In terms of bonding performance measured by wood failure percentage (WFP), most samples under various treatment conditions showed WFP ≥ 80% except for samples under wet condition with WFP ≤ 60%.